Social skills and behavior autism spectrum disorder during covid-19 Pandemic - Imam Mujahid (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
The research aims to describe the social development and behavior of autistic children and find ways to develop the social skills and behavior of autistic children during the COVID-19 pandemic. The research method is qualitative research. The data ware collected using interviews, documentation studies, and observations on parents and special assistant teachers for children with autism spectrum disorders of primary and secondary school age. Check the validity of the data used source triangulation. The results showed that autistic children during this pandemic experienced a decline in behavioral, social, and communication aspects. The method that is considered effective in overcoming this is by using daily activities for the development of social skills and behavior. The components of these activities are 1). Creating communication using verbal and visual language. 2). Develop new routines by forming new habits. 3). Monitor the mental development and physical health of children. 4). Establish regular collaboration and communication with schools. 5). Utilize existing human resources at home. 6). Literacy practice in children. 7). Always involve children in daily activities at home. 8). Encouraging children's social relations to connect with friends and teachers by utilizing technology media.